Hydrological, Geological And Chemical Assessment Of Bouinenc Catchment, South Of France - Samuel Jonson Sutanto (JURNAL SUMBER DAYA AIR, 2010)
Bouinenc catchment assessment has been carried out during field work in the South of France. This catchment assessment consists of field surveying, data collection, measurement, processing, and analysis based on hydrology, geology and chemistry condition. Moreover, EC routing has been done in this catchment along the Bouinenc. Result shows that during the observation period (June 1st until June 8th, 2010), the discharges are decreasing both in Upstream (Chap village) and in the Downstream. EC values at measurement location in downstream are increasing and have diurnal cycle depend on temperature. The potential evapotranspiration varies from above 4 to 7 mm/day during the measurement. Based on the geology map and survey, the majority of this study area is black marls and limestone formation from the Jurassic period. The springs are mainly located in the contact zone of the different layers and also in some cases due to faults. Water type in this area primarily is calcium bicarbonate from the marls and limestone formation. EC routing result shows that there is no significant interaction between surface water and groundwater. In addition, discharges from tributary rivers are not sufficient to influence the main river.